Studi Perencanaan Tanggul Parapet dan Bronjong Sebagai Salah Satu Upaya Penanggulangan Banjir di Sungai Musi Kabupaten Empat Lawang Provinsi Sumatera Selatan - Azmi, Muhammad Haikal; Hendrawan, Andre Primantyo; Sisinggih, Dian (Fakultas Teknik, Universitas Brawijaya, 2022)
During the rainy season, several areas in Empat Lawang Regency are very prone to overflowing water from the Musi River, causing flooding with an average height of 0.2 m-2.0 m, therefore the construction of parapet embankments and gabions is one of the efforts in controlling flood. In this study, a parapet was used with a Q25th return discharge plan of 441.42 m3/s using the Nakayasu Synthesis Unit Hydrograph (HSS) which was then analyzed for unsteady flow hydraulics using HEC-RAS 5.0.7. in the existing condition with the calculation of Q25th with the highest runoff as high as 2.21 m. The results of the planning show that the parapet I building is 1.7 m high, the parapet II building is 2.7 m high, the parapet III building is 3.2 m high, and the gabion building is 4.0 m high. Calculation of stability are controlled under various conditions (overturning, shearing, earthquake, soil bearing capacity). The Budget Plan (RAB) for this construction plan is Rp. 72,939,553,340 (Seventy Two Billion Nine Hundred Thirty Nine Million Five Hundred Fifty Three Thousand Three Hundred Forty Rupiah).Pada saat musim penghujan beberapa daerah pada Kabupaten Empat Lawang sangat rawan terkena luapan air dari Sungai Musi sehingga menyebabkan banjir dengan rata-rata ketinggian 0,2 m-2,0 m, maka dari itu bangunan tanggul parapet dan bronjong menjadi salah satu upaya dalam pengendalian banjir. Dalam penelitian ini digunakan parapet dengan perencanaan debit kala ulang Q25th sebesar 441,42 m3/dt dengan menggunakan Hidrograf Satuan Sintesis (HSS) Nakayasu yang selanjutnya dilakukan analisa hidrolika unsteady flow menggunakan HEC-RAS 5.0.7. pada kondisi eksisting dengan perhitungan Q25th dengan besar limpasan tertinggi setinggi 2,21 m. Hasil perencanaan didapatkan bangunan parapet I tinggi 1,7 m, bangunan parapet II tinggi 2,7 m, bangunan parapet III tinggi 3,2 m, dan bangunan bronjong tinggi 4,0 m. Perhitungan stabilitas terkontrol pada berbagai kondisi (guling, geser, gempa, daya dukung tanah). Rencana Anggaran Biaya (RAB) pada perencanaan konstruksi ini sejumlah Rp. 72.939.553.340 (Tujuh Puluh Dua Milyar Sembilan Ratus Tiga Puluh Sembila Juta Lima Ratus Lima Puluh Tiga Ribu Tiga Ratus Empat Puluh Rupiah).